An analysis of capture fisheries resource depletion in Cirata Reservoir, West Java, Indonesia - ZUZY ANNA (Society for Indonesian Biodiversity, 2018)
Anna Z. 2018. An analysis of capture fisheries resource depletion in Cirata Reservoir, West Java, Indonesia. Biodiversitas 19: 927-935. Fisheries in public waters such as the Cirata Reservoir in West Java, Indonesia are potential economic resources that should not be ignored. They play an important role in food security for the surrounding communities. Unfortunately, natural capture fisheries in Cirata Reservoir have received less attention in the past than aquaculture which dominates economic activity in the waters. Recently, the condition of the dam has deteriorated as a result of major aquaculture activity with extensive use of artificial feedstock; an increase in industrial and domestic waste entering the waters; and open access fisheries management that has allegedly caused depletion of the natural fish resources of the waters. From time to time there have been observed declines in the natural capture fisheries production. The research reported in this paper aimed to estimate the extent of this depletion and associated economic depreciation of capture fish resources in the Cirata Reservoir. Bio-economic methods were used to calculate the potential sustainable utilization of the resources. The analytical model of Logistic Gordon-Schaefer (GS) and Fox models provided the framework for the analysis. The fish depletion was calculated by comparing the potential sustainable utilization and the value of the actual utilization, based on quarterly data for the years 2011 up to 2016. Depreciation was calculated in terms of unit rent loss as a result of the depletion. The analysis showed that depletion of fish resources occurred in certain quarters between years of 2011 to 2016. The value of the total depletion over this period for the GS model amounted to 835.13 tons with an estimated value for depreciation of IDR 5.93 Billion, or IDR 84.71 Billion in Present Value term. For Fox Model, the depletion reaches 1421.35 Ton, with a value of IDR 10.09 Billion, or 144.17 Billion in Present Value term. This value represents the economic loss due to depletion of the fisheries resource in Cirata Reservoir. The policy implication of this fish depletion is that there is a need for better management of the aquatic habitat, by reducing water pollution load, and by regulation of capture fisheries through input/output restrictions based on the conceptual tools of Maximum Sustainable Yield (MSY) and Maximum Economic Yield (MEY).